2007
DOI: 10.1007/s11104-006-9102-7
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron X-ray absorption-edge computed microtomography imaging of thallium compartmentalization in Iberis intermedia

Abstract: Thallium is an extremely toxic metal which, due to its similarities to K, is readily taken up by plants grown in Tl-contaminated soils. Thallium is also a precious metal nearly as economically valuable as gold. Thallium is efficiently hyperaccumulated in Iberis intermedia as aqueous Tl(I) with highest concentrations within the vascular network of leaves. In this study we examine the utility of synchrotron X-ray differential absorption-edge computed microtomography (CMT) in determining the distribution and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…Many of the earlier studies focused on hyperaccumulator plants that are able to accumulate large concentrations of metals or metalloids. These studies revealed, for example, Cd and Zn accumulation in the trichomes of Arabidopsis halleri [27,28], Zn in the epidermal cells of the leaves of pennycress (Thlaspi praecox) [9], Ni in the trichomes [29] and the epidermal vacuoles [22] of Alyssum species, Se in the trichomes of milkvetch (Astragalus bisulcatus) [30], As in the vacuoles of Chinese brake fern (Pteris vittata) fronds [31], and Tl in the veins of candytuft (Iberis intermedia) leaves [32]. More recently, there has been a shift in attention to studying essential or toxic trace elements in non-hyperaccumulator plants: some examples are described below.…”
Section: Trends In Plant Sciencementioning
confidence: 99%
“…Many of the earlier studies focused on hyperaccumulator plants that are able to accumulate large concentrations of metals or metalloids. These studies revealed, for example, Cd and Zn accumulation in the trichomes of Arabidopsis halleri [27,28], Zn in the epidermal cells of the leaves of pennycress (Thlaspi praecox) [9], Ni in the trichomes [29] and the epidermal vacuoles [22] of Alyssum species, Se in the trichomes of milkvetch (Astragalus bisulcatus) [30], As in the vacuoles of Chinese brake fern (Pteris vittata) fronds [31], and Tl in the veins of candytuft (Iberis intermedia) leaves [32]. More recently, there has been a shift in attention to studying essential or toxic trace elements in non-hyperaccumulator plants: some examples are described below.…”
Section: Trends In Plant Sciencementioning
confidence: 99%
“…Spectroscopic methods include proton-induced X-ray emission (PIXE) that targets the embryo region (Mazzolini et al 1985), scanning and transmission electron microscopy (STEM) in combination with energy dispersive X-ray microanalysis (EDX) that focuses on aleurone and scutellum cells to provide subcellular information (Ockenden et al 2004;Lombi et al 2010), nanosecondary ion mass spectrometry (nano-SIMS) that visualizes the subcellular distribution but is limited to regions of only a few mm 2 (Moore et al 2010), and the X-ray fluorescence ((-XRF) method that provides elemental maps for various elements in whole grain sections (Lombi et al 2009;Takahashi et al 2009). The nondestructive m-XRF technique permits a three-dimensional reconstruction of accumulation patterns and can also distinguish between ionic valencies, critical for accumulation of toxic forms of various ions (Scheckel et al 2007). More recently, Ryan et al (2010) developed a large energy-dispersive detector array called, Maia, to capture intricate detail in natural material, together with faster acquisition and improved counting statistics in elemental imaging.…”
Section: B Distribution Of Iron and Zinc In The Seedmentioning
confidence: 99%
“…Computed microtomographic (CMT) imaging has been widely used in the fields of soil science, hydrology, petroleum engineering, and environmental engineering. In petroleum engineering, the focus has often been on extraction of porosity, pore morphology, network information, and relative permeability estimates for use in pore network simulators (e.g., Coles et al, 1998;Lindquist and Venkatarangan, 1999;Turner et al, 2004;Prodanović et al, 2007), whereas in soils and hydrology research, more work has focused on multiphase variables and on estimating properties such as fluid saturation and distribution (e.g., Hopmans, 1999, 2000;Perret et al, 2000); on describing soil structural features such as macropores (e.g., Anderson et al, 1990;Peth et al, 2008;Luo et al, 2010), root structure (e.g., Kaestner et al, 2006;Tracy et al, 2010), and plant uptake mechanisms (e.g., Scheckel et al, 2007). We refer to Taina et al (2008) for an extensive review of tomography applications in soil science, and to Werth et al (2010) for contaminant hydrology-type applications.…”
Section: Multiphase Flowmentioning
confidence: 99%